Carcinogenic etheno DNA adducts in alcoholic liver disease: correlation with Cytochrome P-4502E1 and fibrosis - Mueller, Sebastian; Peccerella, Teresa; Qin, Hua; Glassen, Katharina; Waldherr, Rüdiger; Flechtenmacher, Christa; Straub, Beate Katharina; Millonig, Gunda; Bruckner, Thomas; Seitz, Helmut K. (Alcoholism, 2018)
Background: One mechanism by which alcoholic liver disease (ALD) progresses is oxidative stress and the generation of reactive oxygen species, among others due to the induction of cytochrome P-4502E1 (CYP2E1). Experimental data underline the key role of CYP2E1 because ALD could be partially prevented in rats by the administration of the specific CYP2E1 inhibitor chlormethiazole. As CYP2E1 is linked to the formation of carcinogenic etheno DNA adducts in ALD patients, a causal role of alcohol-induced CYP2E1 in hepatocarcinogenesis is implicated. The purpose of this study was to investigate CYP2E1 induction in ALD, and its correlation with oxidative DNA lesions and with hepatic histology. Methods: Hepatic biopsies from 97 patients diagnosed with ALD were histologically scored for steatosis, inflammation, and fibrosis. CYP2E1 and the exocyclic etheno DNA adduct 1,N6-etheno-2′deoxyadenosine (εdA) were determined immunohistochemically. In addition, in 42 patients, 8-hydroxydeoxyguanosine (8-OHdG) was also evaluated using immunohistochemistry. Results: A significant positive correlation was found between CYP2E1 and εdA (p < 0.0001) as well as between CYP2E1 and 8-OHdG (p = 0.039). Both CYP2E1 (p = 0.0094) and ɛdA (p < 0.0001) also correlated significantly with the stage of hepatic fibrosis. Furthermore, a significant correlation between the fibrosis stage and the grade of lobular inflammation (p < 0.0001) was observed. However, the amount of alcohol consumed did not correlate with any of the parameters determined. Conclusions: These data suggest an important role of CYP2E1 in the generation of εdA, in the fibrotic progression of ALD, and thus in alcohol-mediated hepatocarcinogenesis. CYP2E1 may be a target in the treatment of ALD and a potential prognostic marker for disease progression.